An Unusual Exhibit of Cervical Plasmacytoma with Trademarks of Cervical Myelopathy - Giri, Shilpa; Gurung, Pritam; Shrestha, Bishal; Shrestha, Pranaya; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
We reported a case of a 76-year-old man presented with cervical neck pain since 16 days. He had also weakness of all limbs since 4 days, insidious in onset. MRI Cervical spine revealed an expansile lesion in C2-C3 vertebral level and C2 lamina pathological fracture. He was suspected as a case of multiple myeloma. However, the histopathology report revealed morphological features compatible with Plasmacytoma.